Edmund Bojanowski jako badacz historii regionu - Puślecki, Łukasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article presents works of Edmund Bojanowski about historical research of region. The author focused on those of Bojanowski’s texts, which were related to the region Gostyń Land where he came from. Two articles which are very important for regional research were analysed: Kasper Miaskowski and Do malowniczej podróży po Wielko-Polsce. Gostyń i jego okolica. In the first article he reminds the figure of distinguish poet that inspired many authors to the further research of the biography and work of Miaskowski. Article about Gostyń and its area is touringdescription kept in travel literature style. This extremely interesting and raising many of the issues text is still one of the main sources for the history of Gostyń region. The articles which are analysed here make it possible to consider E. Bojanowski as a precursor of regional study of history concerning Gostyń Land. Numerous reprints are evidence of the quality of these texts.